COVID Stress among Nepal Police Officers - Rajbhandari, Bibek; Tiwari, Bhuwaneshwar; Gurung , Minani; Poudel , Lisasha; Adhikari , Anurag; Shilpakar, Olita; Puri, Rajesh Raj; Singh, Sumi (Journal of Nepal Health Research Council, 2021)
Background: In Nepal, the stress factor is exacerbated by a large number of police officers working away from home with less family contact, a hectic work schedule in a pandemic situation, companions suffering from illness and updates on additional cases with rising mortality rates, and a lack of access to Personal Protection Equipment. The main aim of this study was to identify the prevalence of COVID stress among Nepal police officers working during pandemic.Methods: We conducted a cross-sectional study among police officers (n=1526) working during pandemic in Province X Nepal. Semi-structured questionnaire was administered using google form. COVID Stress Scale -36 (CSS-36) was used to assess the stress in officers. Data collection was done after obtaining ethical approval. Data cleaning was done using a python script and then was exported to Ms. Excel for graph analysis.Results: The highest percentage was seen in the xenophobia subscale (24.63%), followed by contamination (20.10 %) and compulsive checking (19.21%). Comparing socio-demographic variables, 18-27 aged groups including male officers and unmarried groups had experienced high COVID stress. Conclusions: Most of the officers feared from the foreigners perceiving them the main source of COVID-19. Fears about getting contaminated related to COVID-19 was also seen high. There is a need to assess psychological issues and provide social support to police officers during this pandemic situation.Keywords: COVID-19; police officer; stress; Nepal